Complementary Unipolar WS2 Field‐Effect Transistors Using Fermi‐Level Depinning Layers. (15th December 2015) - Park, Woojin; Kim, Yonghun; Jung, Ukjin; Yang, Jin Ho; Cho, Chunhum; Kim, Yun Ji; Hasan, Syed Mohammad Najib; Kim, Hyun Gu; Lee, Han Bo Ram; Lee, Byoung Hun
Abstract : High contact resistance and symmetrical conduction are serious challenges in practical applications of transition metal dichalcogenide (TMD) field‐effect transistors (FETs). Unipolar behavior and reduced contact resistance are achieved for tungsten disulfide (WS2 ) FETs by using a TiO2 interfacial layer inserted between a metal layer and a WS2 layer.